2016
DOI: 10.4049/jimmunol.1502378
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Early- and Late-Response Genes in Acute Pancreatitis

Abstract: Chromatin remodeling seems to regulate the patterns of proinflammatory genes. Our aim was to provide new insights into the epigenetic mechanisms that control transcriptional activation of early- and late-response genes in initiation and development of severe acute pancreatitis as a model of acute inflammation. Chromatin changes were studied by chromatin immunoprecipitation analysis, nucleosome positioning, and determination of histone modifications in promoters of proinflammatory genes in vivo in the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Myocardial I/R injury is an extremely complex and common pathophysiological phenomenon. Egr-1 is associated with pathological changes in I/R injury and is thought to be a “a master switch” for I/R injury because of its regulation of inflammation, coagulation, and vascular hyper-permeability which are thought to be central to pathogenesis of I/R injury ( Yan et al, 2000 ; Zins et al, 2014 ; Sandoval et al, 2016 ). Oxidative stress also be pivotal to the pathogenesis of I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial I/R injury is an extremely complex and common pathophysiological phenomenon. Egr-1 is associated with pathological changes in I/R injury and is thought to be a “a master switch” for I/R injury because of its regulation of inflammation, coagulation, and vascular hyper-permeability which are thought to be central to pathogenesis of I/R injury ( Yan et al, 2000 ; Zins et al, 2014 ; Sandoval et al, 2016 ). Oxidative stress also be pivotal to the pathogenesis of I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of early-and late-response gene clusters in this system is reminiscent of primary and secondary responses observed in other systems, such as the inflammatory response in immune cells [58][59][60][61][62][63] and the growth factor response promoting differentiation and proliferation 64 . Variation in response times can stem from differences in genomic and regulatory features, including the degree to which products are regulated at transcriptional, post-transcriptional and translational levels, the baseline differences in RNA polymerase II occupancy at transcription start sites, and the dependency of target gene regulation on epigenetic modifications 64 .…”
Section: Discussionmentioning
confidence: 67%
“…among these genes, the transcription factor egr1 has a very close relationship with aP. For example, Sandoval et al (41) observed that Egr1 was expressed at high levels in the early inflammatory reaction of aP, and Ji et al (11) demonstrated that after initiating caerulein-induced aP in mice, the severity of aP in egr1 gene-deficient mice was significantly lower compared with that in normal mice. Their study suggested that egr1 may be a key regulator of early development of aP.…”
Section: Discussionmentioning
confidence: 99%